Characterization of optical and nonlinear properties of individual GaP nanowires using optical tweezers. Issue 1 (1st February 2022) - Bolshakov, Alexey D.; Shishkin, Ivan; Machnev, Andrey; Petrov, Mikhail I.; Kirilenko, Demid; Fedorov, Vladimir V.; Mukhin, Ivan S.; Ginzburg, Pavel
Abstract: Semiconductor nanowires (NWs) offer multiple advantages for designing novel optoelectronic devices, such as small footprint, high quantum efficiency, high nonlinear susceptibility. Gallium phosphide (GaP) is one of the attractive materials owing to its low optical absorption and high nonlinear susceptibility. However NWs should be transferred to planar substrates for optical studies, which do not allow efficient signal outcoupling. We demonstrate efficient second harmonic generation in individual GaP nanowires trapped using optical tweezers. Such vertically arranged configuration of NW allows to both efficiently generate second harmonic and to probe linear optical response using broadband light source. Such experiment allows to examine interplay between harmonic generation efficiency and NW dimensions.